1995
DOI: 10.1007/bf03401551
|View full text |Cite
|
Sign up to set email alerts
|

Nramp Transfection Transfers Ity/Lsh/Bcg-Related Pleiotropic Effects on Macrophage Activation: Influence on Oxidative Burst and Nitric Oxide Pathways

Abstract: Background: The Ity/Lsh/Bcg gene on mouse chromosome 1 regulates priming/activation of macrophages for antimicrobial and tumouricidal activity. A candidate gene expressed in macrophages has been identified by positional cloning and full-length sequence analysis, and encodes the Natural resistance-associated macrophage protein (Nramp). In this study, we have tested the hy-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
85
0
9

Year Published

1998
1998
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(95 citation statements)
references
References 34 publications
(41 reference statements)
1
85
0
9
Order By: Relevance
“…23 Instead, allele 7 (or the variant (GT) 11 allele) was found in both studies at a frequency of 0.032 and 0.049, respectively. It has the sequence t(gt) 5 ac (gt) 5 aT(gt) 11 ggcaga(g) 6 and differs by a single nucleotide from allele 1 (the classical (GT) 11 allele) that has the sequence t(gt) 5 ac(gt) 5 aC(gt) 11 ggcaga(g) 6 . These two alleles have the same fragment length and can easily be distinguished by restriction analysis using RsaI.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…23 Instead, allele 7 (or the variant (GT) 11 allele) was found in both studies at a frequency of 0.032 and 0.049, respectively. It has the sequence t(gt) 5 ac (gt) 5 aT(gt) 11 ggcaga(g) 6 and differs by a single nucleotide from allele 1 (the classical (GT) 11 allele) that has the sequence t(gt) 5 ac(gt) 5 aC(gt) 11 ggcaga(g) 6 . These two alleles have the same fragment length and can easily be distinguished by restriction analysis using RsaI.…”
Section: Resultsmentioning
confidence: 77%
“…It was shown that Slc11a1 could regulate and act early in the macrophage activation for antimicrobial activity. [10][11][12][13] This led to the speculation that variants of human SLC11A1 might play a role in controlling resistance to some intracellular infections in humans.…”
Section: Introductionmentioning
confidence: 99%
“…The murine macrophage cell lines RAW 246.7, wildtype (WT) RAW 7.5R, and RAW 10S were a kind gift from J. M. Blackwell (Cambridge University, Cambridge, U.K.). The 7.5R and 10S lines are stable transfectants, the generation of which has been described previously (22). These were cultured in RPMI (Life Technologies) supplemented with 10% FCS and 2 mM glutamine.…”
Section: Cells and Bacteriamentioning
confidence: 99%
“…The actual immunological function of Nramp-1 is not clear except for some indications that it inhibits bacterial growth in reticuloendothelial tissues in an early phase of infection. The mechanism is supposed to operate by modulation of the cytocidal activity of macrophages by enhancing the production of nitric oxide, phagolysosomal fusion, cytokine production and expression of class II MHC molecules [6,46]. There is a link between Nramp-1 polymorphism and differences in mortality after salmonella infection in the chicken [57].…”
Section: Other Proteins Associatedmentioning
confidence: 99%